IMPLEMENTASI PENERBITAN SURAT LAIK OPERASI (SLO) KAPAL PERIKANAN DI PELABUHAN PERIKANAN PANTAI TAMPERAN KABUPATEN PACITAN (STUDI PERMEN KP NOMOR 1/PERMEN-KP/2017) - Malik , Djamaludin; Mudiyanto, Mudiyanto; Saktiono , Maxima Ari (Majalah Ilmiah Gema Maritim, 2022)
This study aims to determine the implementation of the issuance of a Letter of Operational Eligibility (SLO) for Fishing Vessels at the Tamperan Coastal Fishing Port, Pacitan Regency. The research method uses qualitative research methods. Based on the results of observations and interviews, the results of the research are that communication can determine the success of achieving the objectives of the implementation of public policies, the availability of the number of human resources as an SDKP supervisory task force is adequate. Commitment is evidenced by looking at the reasons for the implementor. The goal is to be able to carry out the implementation, the goals /changes to be achieved, and the changes that have been achieved by the implementers for the implementation of the policy of issuing SLO fishing vessels.